Triathletes' motivational dimensions for participation in Ironman, and comparison of these factors with their life satisfaction and achievement perceptions - Çetin, A. (International Journal of Human Movement and Sports Sciences, 2019)
This study aims to examine runners' motivation factors to participate in the Ironman Events and the comparison of these factors with their life satisfaction and success perceptions. The sample of the study were 81,8 % male (n: 112) and 18.2 % female (n: 25) participants who are randomly selected from Ironman Turkey Event in 2018. In the research, "Life Satisfaction Scale"; "Achievement Perception Scale", and "The Motivational Factor Scale for Participating Ultra Marathon" are used as data collection tool in the research. The relations between motivation, life satisfaction and achievement perception are tested with factor analysis, correlation analysis and SEM Partial Least Squares. The results show that motivation has a positive and high relationship with life satisfaction and achievement perception. As a result of the path analysis, there is a significant relationship between motivation dimensions including meaning in life, personal achievement goals and recognition sub-dimensions have a positive and significant effect on life satisfaction. Moreover, health perception has a positive and significant effect on achievement perception. In conclusion, most of the participants were male, the majority of the participants were aged 31 and older and had high income group, university education, working in the private sector, living in the city. It was concluded that the individuals who participated in the Ironman event were individuals who completed their education and worked in the private sector in the business world, who had high income groups and mostly lived in cities. It can be reported that triathletes' high motivational perceptions result in life satisfaction and achievement perception. It can be pointed out that triathletes' high motivational perceptions result in life satisfaction and achievement perception.